Underlying Mechanisms and Candidate Drugs for COVID-19 Based on the Connectivity Map Database - Li, Zhonglin; Yang, Ling (Frontiers in Genetics, 2020)
Background: Coronavirus disease 2019 (COVID-19) has become a worldwide public health crisis. Until now, there are no effective antivirus drugs or vaccines specifically used for its treatment. The connectivity map (Cmap) is a database including gene expression profiles of various human cell lines that are disposed in different small molecules. Candidate drugs can be found by uploading the transcriptome profiles of COVID-19 patients. Previous reports indicated that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and SARS-CoV are highly homologous and both use angiotensin-converting enzyme 2 (ACE2) as the receptor to enter cells. ACE2 protects from various pulmonary diseases, including acute respiratory distress syndrome (ARDS), acute lung injury, pulmonary hypertension, asthma, and chronic obstructive pulmonary disease. While SARS-CoV infection reduces the ACE2 expression in lung. Therefore, the analysis of genes co-expressed with ACE2 in lung may discover the underlying mechanism of COVID-19. Method: Based on the differentially expressed genes (DEGs) of the RNAs isolated from the bronchoalveolar lavage fluid (BALF) of COVID-19 patients, we did functional enrichment analysis and hub gene cluster analysis. Furthermore, we analyzed the co-expressed genes of ACE2 in the normal lung samples and analyst the significant genes. Subsequently, to identify several candidate drugs for the treatment of COVID-19, a search query of DEGs or the co-expressed genes of ACE2 was explored by using CMap. Results&Conclusion: The up-regulated genes of BALF of patients are related to viral mRNA translation. The down-regulated genes of BALF are enriched in immune response. The positively correlated genes of ACE2 are related to immune defense. The negatively correlated genes are enriched in synaptic transmission. Based on CMap, we discovered candidate drugs such as amantadine and aciclovir for the treatment of COVID-19.